Utilização de cagaita, jabuticaba e pitaya na elaboração de fermentado alcoólico e vinagre - Souza, Angélica Cristina de (2015)
Fermented beverages from different fruits are being developed as an alternative to avoid postharvest waste, as well as providing beneficial effects to human health, including the prevention and treatments of diseases. The objectives of this work, were create fermented beverages from different fruits as cagaita (Eugenia ysenterica), jabuticaba (Myrciaria jaboticaba) and pitaya (Hylocereus undatus), determine the antioxidant potential of fermented and rate the fermented alcoholic jabuticaba potential for the production of vinegar with immobilized acetic bacteria. In the first stage of the study, to produce the fermented beverage was used the yeast Saccharomyces cerevisiae CCMA 0200 and the fermentations were monitored daily, assessing the number of viable cells in suspension, ph, degree Brix and chromatographic analysis. In the end of fermentation, the drinks were analyzed for their content of phenolic compounds, antioxidant activity in vitro, DPPH, FRAP and quantitation of individual phenolic compounds. The content of ethanol at the end of the fermentation process were: 62,26 g.L -1 (7,9 ºGL) in cagaita juice, 67,3 g.L -1 (8,5 ºGL) in jabuticaba juice and 75,2 g.L -1 (9,5 ºGL) in pitaya juice. By principal component analysis (PCA), it was possible to differentiate the three fermented fruit according to 25 quantified volatiles: aldehydes, alcohol, higher alcohols, terpene, acetate, dieter, furan, volatile fatty acids, ketone and ethyl ester. The Cagaita fermented stood out with higher content of total phenolic ability to attract free radicals DPPH ,in addition to reducing power measured by FRAP method. In the second stage of the study, was produced the jabuticaba vinegar (Myrciaria jaboticaba). Firstly, alcoholic fermentation was realized, and then, acetic fermentation, to the vinegar production, using mixed culture of immobilized acetic bacteria Acetobacter aceti (CCT 0190) and Gluconobacter oxydans (CCMA 0350). The wine obtained show 74.78 g.L -1 of ethanol, after 168 hours of fermentation. The yield of acetic acid was 74,4% and productivity 0,29 g.L -1 .h -1. The amounts of citric acid (6.67 g L -1 ), malic acid ( 7.02 g L -1 ) and succinic acid (5.60 g L -1 ) in the vinegar were particularly high. These organics acid are important to give taste and flavour to the vinegar. Fermented cagaita, jabuticaba and pitaya have presented polyphenols and show antioxidant capacity; therefore, they are sources of bioactive substances. The vinegar can be successfully produced from jabuticaba fermented alcoholic using mixed culture of A. aceti and G. oxydans immobilized.